Meningkatkan Motorik Halus Anak Kelompok B Melalui Kegiatan Membatik Ecoprint di TK Cempaka Glantangan Kecamatan Tempurejo Kabupaten Jember - Wardana, Atika; Putra , Wijaya Adi; Sugiarto, Muhammad Agus (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to determine the improvement of fine motor skills in group B children at TK Cempaka Glantangan, located in Tempurejo District, Jember Regency, through Ecoprint batik-making activities. The type of research used in this study is Classroom Action Research (CAR). The subjects of this study were group B students at TK Cempaka Glantangan, totaling 29 children, consisting of 7 boys and 22 girls. The results of the study showed that the implementation of Ecoprint batik-making activities in cycle I achieved a percentage of 41.37%, which falls under the "Starting to Develop" (MB) category. In cycle II, the implementation of Ecoprint batik-making activities increased significantly, reaching 89.65%, and fell into the "Developing as Expected" (BSH) category. Based on the final results, it can be concluded that the Ecoprint batik-making activity has a positive impact on the improvement of fine motor skills in young children. These improvements include better hand coordination, finger dexterity, and focus during creative tasks. Thus, Ecoprint batik-making can be an effective and engaging learning method that supports the development of fine motor skills in early childhood education, especially for group B students at TK Cempaka Glantangan in Tempurejo District, Jember Regency.